'Maybe it's culture and maybe it isn't': An ethnographic study of sensemaking, culture and performance in a multicultural team. Issue 2 (April 2023) - Means, Ann; Mackenzie Davey, Kate
Links between cultural diversity and team performance remain unclear despite extensive research. This study critiques essentialist 'Input-Process-Output' logics to focus on team members' sensemaking. Using observation and interview data from an ethnographic study of an Indian-German team over an 18-month high-pressure project, we used thematic analysis and event sequencing to map sensemaking of culture and performance over time. Team members initially constructed a prospective frame linking stereotypes of cultural difference to performance, which plausibly explained problems while protecting identity. This frame proved resistant to updating. While overt conflict was avoided, the failure to confront difficulties closed down alternative explanations and prevented innovation and learning. Team performance was evaluated both positively and negatively reflecting ongoing ambiguity around performance. The role of culture in performance was only challenged post-project after time for reflection. The longitudinal, ethnographic approach enables this research to contribute to sensemaking by demonstrating the importance of prospective framing and highlighting the role of identity and plausibility in resisting updating frames. We argue that essentialist conceptions of the unequivocal positive or negative outcome of cultural diversity as 'double-edged sword' should be reframed to stress agency and the importance of facilitating conditions for learning in multicultural teams.